PENGARUH STRUKTUR MODAL (DER) DAN PROFITABILITAS (ROA) TERHADAP NILAI PERUSAHAAN (PBV) PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2015-2019 - Isman Hapid; Hanifah Hanifah (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2022)
The value of the company is the price that will be handed over to the buyer (investor) if the company's shares are sold. The greater the value of the company, the greater the share price. This study aims to examine the effect of Capital Structure and Profitability on Firm Value in Food and Beverage Sub-Sector Companies listed on the Indonesia Stock Exchange.The data used is secondary data with documentation method in the form of annual financial reports. The population in this study amounted to 55 food and beverage companies and samples were taken using purposive sampling as many as 11 companies. The analysis technique used is classical assumption test, multiple linear regression, coefficient of determination test and hypothesis testing using SPSS v 25The results of the first study are Capital Structure with a significant value of (0.000 0.05) and tcount ttable (7.673 2.00575) meaning that Capital Structure has a significant influence on Firm Value, then Profitability shows a significant value of (0.000 0.05) and tcount ttable (6,894 2,00575) means that profitability has a significant effect on firm value. The coefficient of determination shows a value of 70.4% while the remaining 29.6% is influenced by other factors. The results of the F test show a simultaneous significance value of 0.000 0.05 and fcount ftable (61.750 3.18) meaning that Capital Structure and Profitability simultaneously have a significant effect on Firm Value.